2016
DOI: 10.1007/s11270-016-2966-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Heavy Metals and Total Petroleum Hydrocarbons on Soil Bacterial Activity and Functional Diversity in the Upper Silesia Industrial Region (Poland)

Abstract: Various inorganic and organic pollutants in industrial soils may adversely affect soil microorganisms and terrestrial ecosystem functioning. The aim of the study was to explore the relationship between the microbial activity, microbial biomass, and functional diversity of soil bacteria and the metals and total petroleum hydrocarbons (TPHs) in the Upper Silesian Industrial Region (Poland). We collected soil samples in pine-dominated forest stands and analyzed them according to a range of soil physicochemical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 45 publications
2
20
1
Order By: Relevance
“…Muñiz et al (2014) noted that Cd in an exposed microbial community modified the physiological profile of the microorganisms. Klimek et al (2016) reported the negative relationship between total petroleum hydrocarbons (TPH) and functional soil bacterial diversity (CLPP). The effect is indicative of a significantly decreased or increased rate of cell proliferations resulting from the short-or long-term contact of bacteria with the metals (Piotrowska-Seget and Kozdrój, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muñiz et al (2014) noted that Cd in an exposed microbial community modified the physiological profile of the microorganisms. Klimek et al (2016) reported the negative relationship between total petroleum hydrocarbons (TPH) and functional soil bacterial diversity (CLPP). The effect is indicative of a significantly decreased or increased rate of cell proliferations resulting from the short-or long-term contact of bacteria with the metals (Piotrowska-Seget and Kozdrój, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, the Pb and Cd concentrations in the studied soil (CT) were significantly higher (1 409.91 -6 887.87 mg kg -1 -Pb; 1-147.27 mg kg -1 -Cd). Klimek et al (2016) suggest that the metal concentration in soils from the Upper Silesian region (Olkusz and Miasteczko Śląskie) are 1 577 mg Pb kg -1 and 5437 mg Zn kg -1 . In conclusion, the concentration of heavy metals in the studied soils was higher in comparison to the earlier studies carried out in the Upper Silesian region (Biernacka and Małuszyński, 2006;Klimek et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Metals are toxic to microorganisms by replacement of essential metals, damaging cell membrane and cellular function disruption . Thus, lower catabolic functions of microorganisms in metal-contaminated soils were well documented (Boshoff et al 2014;Klimek et al 2016). In addition, carbon resources are considered as the driving force for microbial density and activity (Burton et al 2010).…”
Section: Effects Of S Alfredii Growth On Soil Microbial Metabolic Fumentioning
confidence: 99%
“…For Cd and Pb analysis milk samples were digested in a MARS 6 (CEM Corporation, Matthews, USA) using MARSX press tubes. A total of 0.5 g of lyophilized raw milk sample was added, and 10 mL of 65% PA nitric acid (Vetec, Rio de Janeiro, Brazil) was added according to the methodology described by Klimek et al (9) . The digestion was performed between 180 °C and 210 °C, with a ramp time of 20 to 25 minutes, and a hold time of 15 minutes, as recommended by the manufacturer for organic samples.…”
Section: Methodsmentioning
confidence: 99%